Improving dietary quality and livelihoods using farm and wild biodiversity through an integrated community based approach in Loima and Turkana South, subcounty, Turkana County, Kenya - Oduor, Francis; Induli, Irene; Keding, Gudrun; Jordan, Irmgard; Termote, Celine (2023)
Despite the significant progress made in addressing food insecurity and malnutrition in Kenya, the problem remains pervasive in Turkana . At the same time, threats of climate change and other risk like Covid 19 have worsened the bleak situation beyond its adaptive limits. Therefore, a genuine need for building interventions that are both responsive to local contexts and resilient to ensure long term development is apparent. This requires the recognition of indigenous resources including local knowledge to be factored in the design of interventions to enhance the resilience of the communities. Against this background, the ImproDiet-CoProject applied the Participatory Approach for Diet and Farm Diversity developed by Bioversity International in Vihiga County, Kenya, to support the communities to enhance their resilience and transition to healthier and more diverse diets.